The Canadian Federal Government and Normativity Transformations: Towards a Reconfiguration of Governmentality in Canada? - Rouillard, Christian (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2016)
For several decades, the Canadian federal government has been the subject of many administrative reforms whose nature, scale and resources vary considerably. The frequency of these reforms increased considerably during the 1990s, although political stability on the federal level was particularly high at the time. By using the normativity-governmentality dynamic as a heuristic model, this article focuses on the Public Service Modernization Act (PSMA) to better understand the effects of the transformation of norms on the modes of interactions and power relationships between actors, institutions and social groups in the Canadian public service context. It questions the way in which transformations in normativity change the conditions of governmentality in Canada. The main thesis of this paper argues that the normative flexibility given to managers (by the PSMA) in the staffing process does not lead to a real increase in their room to manoeuvre, due to: 1) the (re)definition of merit (confusion factor); 2) the concomitant implementation of the Financial Administration Act (inertia factor); and 3) the legacy of previous administrative reforms (the one-step-forward, one-step-back factor).